UPAYA MENINGKATKAN KEPERCAYAAN DIRI PESERTA DIDIK MELALUI METODE ROUND ROBIN CARD PADA MATA PELAJARAN PPKN KELAS X-1 SMA NEGERI 1 PONOROGO - Muzakkiyah Darojat; Oksiana Jatiningsih; Edy Purnomo (Institute Agama Islam Al-Qolam Malang, 2023)
This study aims to increase the self-confidence of students at SMAN 1 Ponorogo by using round robin card and active learning methods. The research method used is a quantitative descriptive method. The research subjects totaled 36 students consisting of 15 male students and 21 female students. Data collection techniques used include observation and documentation in the form of descriptive field notes. The instruments in this study included asking questions, giving opinions during discussions, and conveying ideas in public. Data analysis techniques were carried out using quantitative and qualitative data analysis. The results showed that there was an increase in students' self-confidence from pre-cycle to cycle I by 36.1%. The increase in student self-confidence also occurred in cycle I to cycle II of 27.8%. In this study the round robin card learning method can increase students' self-confidence by 63.9%. The round robin card method with active learning by utilizing video media needs to be done so that students can be more confident in the learning process. The use of media in the form of video or power point can facilitate students in finding an overview of the material to be delivered.